Digital marketing : integrating strategy and tactics with values : a guidebook for executives, managers, and students - Kaufman, Ira Morton, 1947-; Horton, Chris (Routledge, Taylor & Francis Group, 2015)
"Digital Marketing is an easy-to-understand guidebook that helps the reader to adopt a digital mindset, incorporate digital trends strategically, and integrate the most effective digital tools with core values to attain a competitive advantage"--Resumé vydavatele
Terminologický slovník
Keywords: internetový marketing; Internet marketing; příručky; handbooks and manuals